Uma revisão narrativa de centros de convivência dos idosos no Brasil e a história do CCI aconchego da cidade de Botucatu/SP - Silva, Bruna Giovanna Buesso da [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The increase in the life expectancy of Brazilians is a recent phenomenon and brings with it challenges for society. Associated with this change, we verified the progress of technology in the improvement of resources for health care, however, we still find the lack of services that offer older people possibilities to live old age in a more creative way, valuing potentialities, instigating the discovery of capacities unknown, realization of dreams that are behind, dreams of the now and wishes of tomorrow. The National Policy on the Elderly, published in 2003, is the first reference of public policies directed at the elderly, being in this document the first reference to nonasylum services for the elderly, among them, the coexistence centers. The Centers for the Coexistence of the Elderly are places designed to assist the elderly in the morning and afternoon periods, with physical, labor, cultural, recreational, citizenship and associative education activities. We were interested in this study to verify what is available in the literature regarding Centers for the Coexistence of the Elderly in Brazil, for this purpose, we conducted a narrative review of the references found in the health databases. As a complement, we present the process of founding and implementing the Center for the Cohabitation of the Elderly "Aconchego", located in the city of Botucatu, through the collection of historical data from the two founders through semi-open interviews. According to the interviewees the "Aconchego" was founded from the movement of women caregivers in an elderly caregiver training course. The project became feasible from the engagement of those involved in the process of structuring the service, in solving difficulties and challenges that have been encountered until now, but which set new goals to be achieved.

O aumento da expectativa de vida dos brasileiros é um fenômeno recente e traz consigo desafios para a sociedade. Associado a essa mudança, verificamos o avanço da tecnologia no aprimoramento de recursos para atenção à saúde, contudo, ainda encontramos a carência de serviços que ofereçam aos idosos outras possibilidades de viver a velhice de modo mais criativo, valorizando potencialidades, instigando a descoberta de capacidades desconhecidas, concretização de sonhos que ficaram para trás, sonhos do agora e desejos do amanhã. A Política Nacional do Idoso, publicada em 2003, é o primeiro referencial de políticas públicas voltada à pessoa idosa, sendo neste documento a primeira referência a serviços de atendimento não-asilares para idosos, dentre esses, os centros de convivência. Os Centros de Convivência dos Idosos são locais destinados a atender os idosos nos períodos matutino e vespertino, dispondo de atividades físicas, laborais, culturais, recreativas, educação para cidadania e associativas. Interessou-nos neste estudo verificar o que há disponível na literatura a respeito de Centros de Convivência dos Idosos no Brasil, para tanto realizamos uma revisão narrativa das referências encontradas nas bases de dados em saúde. Como complementação, apresentamos o processo de fundação e implantação do Centro de Convivência do Idoso “Aconchego”, localizado no município de Botucatu, por meio do levantamento de dados históricos junto à duas fundadoras, através de entrevistas semiabertas. Segundo as entrevistadas o “Aconchego” foi fundado a partir da movimentação de mulheres cuidadoras em um curso de formação de cuidador de idoso. O projeto se tornou viável a partir do engajamento das envolvidas no processo de estruturação do serviço, na resolução de dificuldades e desafios, até hoje encontrados mas que colocam novos objetivos a serem atingidos.
Keywords: Senior centers; Brazil; Senior; Centro de convivência do idoso; Brasil; Idoso